Human Resource Management Strategy in Flood Mitigation in Cultural Heritage Tourism Areas - Nurtjahjono, Gunawan Eko; Supriono, Supriono; Pambudi, Fahrizal Surya; Prakasa, Yudha (MIX: JURNAL ILMIAH MANAJEMEN, 2026)
Objectives: This study aims to analyze the human resource (HR) management strategy of the Semarang City Government in flood mitigation efforts in the Old City cultural heritage area. Although various technical measures have been implemented, the effectiveness of flood mitigation still depends heavily on the quality, coordination, and preparedness of the human resources involved.Methodology: This research uses a descriptive qualitative approach with data collection techniques through interviews, observations, and documentation studies. Data analysis was conducted in four stages: data collection, data condensation, data presentation, and drawing conclusions.Finding: The research results show that the Semarang City Government has implemented several stages of disaster mitigation, including documentation of cultural heritage assets, threat assessments, and flood prevention measures through the construction of polders and pump houses. However, weaknesses were still found in the vulnerability assessment stage, which lacked support from conservation experts and a solid cross-agency coordination system.Conclusion: Overall, the human resource management strategy for flood mitigation in Kota Lama has been quite successful, but not yet optimal. Strengthening employee capacity, increasing inter-agency collaboration, and empowering the community are key to maintaining the sustainability of cultural heritage tourism destinations from the threat of flooding.